Contextualization of Hadith About Music: Perspectives of Hadith Scholars and Dilthey's Hermeneutics - Ichwahyudi, Budi; Alim, Brilian; Hidayatul, Aida; Rahma, Febi (Sekolah Tinggi Agama Islam Sumatera Medan, 2024)
Differences of opinion regarding the laws of music in Islam continue to be debated in modern society. Music, which is now developing rapidly, has a complex role, not only as entertainment but also as a means of therapy and social expression. On the other hand, there are hadiths that textually appear to prohibit music, giving rise to diverse interpretations. This study aims to analyze the understanding of the hadith about music by using Wilhelm Dilthey's hermeneutics theory, which emphasizes the importance of understanding the text in its social, cultural, and historical context. This study uses a qualitative method with a hermeneutics approach to explore the meaning of the hadith about music in its context of time and place. The results show that the application of Dilthey's hermeneutics allows for a more contextual and historical understanding of the hadith. The prohibition in the hadith about music is more related to the social conditions of the Arab society at that time, where music was often associated with excessive behavior that could lead to sin. By considering the principle of Islamic purpose, music that is used for positive purposes can remain relevant and not contradict Islamic values. The implication of this study is the need for a contextual approach in understanding hadith, so that the resulting interpretation is more in line with the times and the needs of Muslims today.